Prava čeloveka — ot èpohi Prosveŝeniâ do informacionnogo obŝestva - Zołotar, Olha (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The author of the article analyses the origins of human rights from the Enlightenment period to the information society. First, she points to the establishment and development of the idea by Enlightenment thinkers. Speaking of the historical development of human rights, we have to bear in mind that it is not about the emergence or evolution of human rights as such. Their development is determined by socio-political conditions and spatial-temporal factors.Social transformation leading to the emergence of the information society has shaped awareness of human rights in the sense that information and communication technologies should not be regarded as an end in themselves. Next the author examines the problem of informational exclusion or digital divide as well as the impact of the virtual reality on people’s lives in real society.
Keywords: prawa człowieka; społeczeństwo informacyjne